Moore's clinically oriented anatomy - Dalley, Arthur F. II; Agur, Anne M. R. (Wolters Kluwer, 2024)
Clinically Oriented Anatomy is widely acclaimed for its comprehensive and well-written, story-telling text, accurate and detailed illustrations, and the relevance of its clinical correlations (blue boxes). The textbook serves as a complete reference and places clinical emphasis on anatomy that is important in physical diagnosis for primary care, interpretation of diagnostic imaging, and understanding the anatomical basis of emergency medicine and general surgery. This textbook is popular in a variety of programs, including medical, physician assistant, physical therapy, occupational therapy, graduate biology/anatomy, and exercise science--